Susceptibility of Palmistichus elaeisis (Hymenoptera: Eulophidae) to essential oils from Lippia origanoides Cham. (Verbenaceae) and Cymbopogon citratus (DC) Stapf. (Poaceae) - Soares de Aguiar, Caio Victor; Cesarin de Oliveira, Sabrina; Santos Sombra, Kassio Ewerton; Ferreira Rodrigues, Raimundo Henrique; Fagundes Pereira, Fabrício; Pastori, Patrik Luiz (Revista Ceres, 2025)
Palmistichus elaeisis (Hymenoptera: Eulophidae) is a parasitoid with potential for use in control of lepidopteran pests; its integrated use with botanical insecticides may be feasible in pest management. Therefore, the objective was to evaluate the susceptibility of P. elaeisis to the essential oils of pepper-rosemary and lemongrass. The experiment was implemented in a completely randomized design, in a 2 (oils) × 4 (concentrations: 0.125, 0.25, 0.5, and 1.0 %) factorial arrangement, with two controls (detergent and deltamethrin). The following traits were evaluated: parasitism (%) - in the F1 generation, emergence (%), the progeny per pupa, the sex ratio, the longevity of the parental generation of males and females, and the egg-adult period of the parental and F1 generation. There were no significant differences for the biological parameters evaluated regarding the essential oils, thus indicating that the oils were innocuous to P. elaeisis. This result was confirmed by the percentage of emergence of the next generation (F1), which was always greater than 85%. The essential oils also did not affect the percentage of parasitism of the F1 generation. Thus, at the dosages tested, the essential oils of pepper-rosemary and lemongrass are selective agents that do not damage P. elaeisis.